Protection against H5N1 highly pathogenic avian and pandemic (H1N1) 2009 influenza virus infection in cynomolgus monkeys by an inactivated H5N1 whole particle vaccine. - Misako Nakayama (Public Library of Science (PLoS), 2013)
H5N1 highly pathogenic avian influenza virus (HPAIV) infection has been reported in poultry and humans with expanding clade designations. Therefore, a vaccine that induces immunity against a broad spectrum of H5N1 viruses is preferable for pandemic preparedness. We established a second H5N1 vaccine candidate, A/duck/Hokkaido/Vac-3/2007 (Vac-3), in our virus library and examined the efficacy of inactivated whole particles of this strain against two clades of H5N1 HPAIV strains that caused severe morbidity in cynomolgus macaques. Virus propagation in vaccinated macaques infected with either of the H5N1 HPAIV strains was prevented compared with that in unvaccinated macaques. This vaccine also prevented propagation of a pandemic (H1N1) 2009 virus in macaques. In the vaccinated macaques, neutralization activity, which was mainly shown by anti-hemagglutinin antibody, against H5N1 HPAIVs in plasma was detected, but that against H1N1 virus was not detected. However, neuraminidase inhibition activity in plasma and T-lymphocyte responses in lymph nodes against H1N1 virus were detected. Therefore, cross-clade and heterosubtypic protective immunity in macaques consisted of humoral and cellular immunity induced by vaccination with Vac-3.